2020
DOI: 10.1103/physrevb.102.014504
|View full text |Cite
|
Sign up to set email alerts
|

Shapes of rotating normal fluid He3 versus superfluid He4 droplets in molecular beams

Abstract: Previous single-pulse extreme ultraviolet and x-ray coherent diffraction studies revealed that superfluid 4 He droplets obtained in a free jet expansion acquire sizable angular momentum, resulting in significant centrifugal distortion. Similar experiments with normal fluid 3 He droplets may help elucidate the origin of the large degree of rotational excitation and highlight similarities and differences of dynamics in normal and superfluid droplets. Here, we present a comparison of the shapes of isolated 3 He a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Most outlines are ellipses, consistent with spheroidal, rotating droplets ( 8 , 15 , 17 , 21 , 22 ). In previous studies, it was found that a cryogenic fluid expansion into vacuum readily produces rotating 4 He and 3 He droplets ( 15 , 17 ).…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Most outlines are ellipses, consistent with spheroidal, rotating droplets ( 8 , 15 , 17 , 21 , 22 ). In previous studies, it was found that a cryogenic fluid expansion into vacuum readily produces rotating 4 He and 3 He droplets ( 15 , 17 ).…”
Section: Resultsmentioning
confidence: 77%
“…Most outlines are ellipses, consistent with spheroidal, rotating droplets ( 8 , 15 , 17 , 21 , 22 ). In previous studies, it was found that a cryogenic fluid expansion into vacuum readily produces rotating 4 He and 3 He droplets ( 15 , 17 ). It was also found that droplets of different isotopes have very similar average aspect ratios of about 1.05 for their projections on the detector plane ( 17 ).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations